A new Nalassus Mulsant, 1854 (Coleoptera: Tenebrionidae: Helopini), the first representative of the genus from the Russian Far East - Nabozhenko, M.v.; Ivanov, S.n. (Zootaxa, 2015)
A new species, Nalassus (Helopocerodes) olgae sp. n., is described from Primorsky Krai in the Russian Far East. A new combination is established: Nalassus (Helopocerodes) magyari (Kaszab, 1968), comb. n. The new species is similar to N. magyari but differs in the sculpture of the metaventrite, larger body and widely flattened lateral sides of the pronotum.